PENGARUH KONSENTRASI KALSIUM TERHADAP PERTUMBUHAN DAN PRODUKSI DUA VARIETAS TANAMAN MELON (Cucumis melo L.) PADA SISTEM HIDROPONIK MEDIA PADAT - Dewinta Puspita Sari; Yohannes Cahya Ginting; Darwin Pangaribuan (Universitas Lampung, 2013)
The experiment aimed to investigate response of two muskmelon varieties on calcium (ca) concentration of hydrophonic solid media. The experiment was arranged in a factorial completely randomized design. Muskmelon varieties of Clara and Ivory were cultured in hydrophonic solid media with calcium concentration of 100 ppm, 150 ppm, 200 ppm, 250 ppm, and 300 ppm. The results showed that the growth and yield of var. ivory was better than those of var. Clara. Plant response on ca concentration between 100-300 ppm showed a linier curve. Every 10 ppm increment of ca enhanced fruit fresh yield of 9.24 g. Key words: Cucumis melo, hydrophonic, calcium, growth, yield